Performance Analysis of Interchanges and Roads in Pura Besakih, Karangasem District, Bali Province - Decky Cipta Indrashwara; I Nyoman Indra Kumara; Fery Surya Tapa, I Gede (Jurnal Teknik Sipil dan Perencanaan, 2024)
This analysis was conducted to analyze the performance of intersections and sections around Besakih Temple, especially during religious ceremonies. A field traffic data survey was conducted by installing a handycam at a predetermined point to determine the performance of intersections and roads. Furthermore, secondary data collection is carried out to support the completeness of the required traffic data. So that the traffic data is obtained. After the data is collected, the analysis of intersections and roads is carried out. From the results of the study, it is found that (1) the performance of the intersection is: the postal one intersection has a traffic volume of 7305.3 pcu/hour, a capacity of 5367.61 pcu/hour, a degree of saturation of 1.369, a delay of 19.2 seconds, and an intersection service level. C. At Postal Intersection 2, the traffic volume is 4973.5 pcu/hour, the capacity is 2810.24 pcu/hour, the degree of saturation is 1.77, the delay is 22.06 seconds, and the service level of the intersection is D. At Postal Intersection 3, the traffic volume is obtained traffic is 7391.4 pcu/hour, capacity is 3924.02 pcu/hour, degree of saturation is 1.88, delay is 23.19 seconds and the service level of intersection D. So that the average intersection volume exceeds the capacity of the intersection. (2) The performance of the road segment is only sought for the degree of saturation: the Winana road section is 0.67, the Besakih highway is 0.46, the Kedugung highway is 0.25 and the Batusesa highway is 0.048.